Semiotic Analysis on Westin Hotels and Resorts Advertisement Campaigns - Minheere, Peter Wayan; Erfiani, Ni Made Diana; Kamayana, I Gusti Nyoman Putra (LPPM Universitas Dhyana Pura, 2024)
Signs in various forms are often used in various interests in implying certain messages or meanings. In advertising a service, signs are often used to imply the quality of their services, not least in the promotion of hotel services. Therefore, the sign used needs to be in accordance with the purpose of the message to be conveyed. This study aims to identify the meaning of signs and massages in hotel campaigns by using the theory of semiotics by Barthes (1978). The descriptive qualitative method was used to analyze the data. This study used source from six campaigns by Westin Resorts and Hotels. This study analyzed the denotation, connotation, and myth from all the signs found in the campaigns and interpreted the massages. The meaning of the signs found can be interpreted both in the first meaning (denotation) which relates to the direct meaning, the second meaning (connotation) which relates to the context of promotion in each campaign, and the third meaning (myth) which consists of the relation of denotation and connotation meaning in each sign and produces new meaning in each sign. The message in each sign is found through the conclusion and interpretation the relationship between denotation, connotation, and myth in each campaign sign. The myth showed the purpose and impression conveyed in each sign used in each Westin Hotels and Resorts campaign so that it indirectly shows the message contained in the sign. The meaning and the message of the found signs indicate the promotion of Westin Hotels and Resorts with the context of the services offered in each campaign and persuade or influence potential customers to using their services.